Analisis Keoptimalan Jaringan Transmisi Nasional Provinsi Sumatera Barat dengan Algoritma Prim - Nafiha Irsyam; Yusmet Rizal (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — Electricity is one of the main requirement for supporting and compliances the needs of human life. Consumption of electricity continues to increase caused by many residential areas and large industries built also many locations need electricity. Electric power must be developed in line with the increasing demand for electricity, but the installation of electric cables are sometimes inefficient and spending lots of charge. The purpose of this study is to determine the optimal length of electric cables in the national transmission network of West Sumatra. This study begins by representing the map of the National Transmission Network of West Sumatera into a connected, weighted and undirected graph, then determining the minimum spanning tree using Prim Algorithm. The result of this research is electrical cables on the transmission network with Prim Algorithm is more optimal. Keywords — Transmission Network, Optimization, Prim Algorithm.